How to recognize & reward employees : 150 ways to inspire peak performance - Deeprose, Donna (WorkSmart series., 2006)
Recognizing and rewarding employees is a true business imperative no manager can afford to ignore. Now in a revised second edition, "How to Recognize & Reward Employees" gives managers all the helpful tools and information they need to get the most from their people. The book reveals the best ways to improve employee morale, productivity and quality of work, select the right reward for the achievement and inspire both high and low performers. It is an essential reference for every organization.